Evaluation of Microleakage in Fissure Sealants following Contamination with Artificial Saliva at Different Curing Times with or without using bonding agent - Bahman Seraj; Saeedeh Mokhtari; Sara Ghadimi; Fatemeh Ghanaat; Hossein Bagheri (Islamic Dental Association of Iran, 2018)
Background and Aim: One of the important factors in microleakage of fissure sealants is saliva contamination. Researchers believe that applying bonding agents can reduce the microleakage. The present study compared the microleakage of a fissure sealant contaminated with artificial saliva at different curing times with or without using a bonding agent. Materials and Methods: In this in-vitro study, 96 extracted premolars were randomly divided into eight groups. Fissure sealant was applied to all groups; in 4 groups after putting on a bonding agent and in remaining four without a bonding agent. Specimens of each group were contaminated with saliva at different times (5, 10, 15 and 20 sec-onds) during curing. Then the microleakage of samples was measured. Mann-Whitney and Kruskal-Wallis tests were used to statistically analyze the collected data. Results: No-bonding groups had significantly higher microleakage values than bonding groups. Among bonding groups, the microleakage values were significantly lower when contamination occurred after 15 and 20 seconds of light curing. Amounts of microleakage were similar in no-bonding groups (P=0.39) when contamination occurred at 5, 10 and 15 seconds of curing; however, contamination after 20 seconds led to significantly lower microleakage (P<0.001). Conclusion: The findings revealed that when using the bonding agent, retreatment is not required if contamination occurs after 10th second of curing; however, retreatment is required when no bonding has been applied, and contamination happens before 20th s of curing. Thus the isolation is more critical when pits and fissure sealants are applying without using a bonding agent.